The Online Media Practice in Covering Indonesian National Police’s Prevention Efforts on the Prohibited Party's Ideology Spread in Indonesia - Sari, Intan Mustika (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Critical discourse analysis examines the efforts of social forces and ideological interests of a group that are reproduced and defended through texts. The discussion is connected with social contexts that have specific purposes and assumptions. This study focuses on online news reported at liputan6.com site on May 11 th, 2016. This study’s method is a critical discourse analysis introduced by Norman Fairclough with the implementation of transitivity system as the data analysis theory. It aims to uncover the elements of social practice from the aspects of linguistic and discourse. The result indicates the existence of social practice from the online news site in processing information shapes the practice representation conducted by figures who act the discourse which can affect the views of people including their understanding and behavior in social life.